Implementation of The C4.5 Algorithm in Describing The Trends of The Human Consciousness and Unconsciousness - Ronaldo Syahputra; Yeviki Maisyah Putra (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
The human mind has two properties that have different and conflicting functions. The two characteristics of the mind are the conscious mind and the subconscious mind. This study uses the C4.5 data mining algorithm to describe or see the tendency of the conscious and subconscious or the level of suggestion. Suggestibility is the most important thing in hypnotherapy. Hypnotherapy is a therapy performed under hypnosis. Hypnosis is communication with the human subconscious. The C4.5 algorithm for Data Mining is used to form a decision tree. This research will produce a decision tree that can explain the suggestive level of a series of tests that have been carried out. Testing is done with RapidMiner software to get a decision tree. The test consists of a series of tests consisting of four types of tests, where test 1 is to measuring right brain dominance , test 2 is to measure the speed of receiving instructions, test 3 is to measure a person's creativity, and test 4 is to know person's level of understanding, reasoning and imagination. The results of manual calculations were carried out in this study later with the results obtained from the results of testing with the RapidMiner software